Young Children’s Representational Structures of Robots’ Behaviors - Mioduser, David; Kuperman, Asi (Design and Technology Education: An International Journal, 2020)
Despite the fact that the sophisticated technologies are a substantial component of children’s everyday environment, of the space within which they act, play and learn - the world of complex technological systems (their characteristics, and the knowledge and skills involved in operating, designing and programming them) is almost ignored in the preschool and elementary school curriculum. The study reported in this paper is part of a research plan embedded in the implementation of a comprehensive curriculum aiming to support the development of technological thinking in kindergartens, including knowledge and skills in areas such as design, the artifacts in our material culture, smart artifacts and robotic systems, or programming. This particular study aimed to address young children’s (aged 5-8) perception of the adaptive behavior of a robot and the representational structures (or functioning schemes) they adopt to think about how its behaviors are generated and controlled. When children think about the robot’s behavior, they may adopt different perspectives that translate into different representational structures, (e.g., one-time episodic representation; a script that can became a reusable routine; a universal representation such as a rule of behavior). The findings evidence the ability of young children engaged in programming to think in terms of abstract rules and to use these for programming and designing a robot’s behavior.